Early detection and intervention of clonal hematopoiesis for preventing hematological malignancies. (10th July 2022) - Ye, Baixin; Sheng, Yuping; Zhang, Mingming; Hu, Yongxian; Huang, He
Abstract: Clonal hematopoiesis (CH) is a clonal expansion of single hematopoietic stem cells (HSC) with germline or somatic mutations accumulated in specific genes, which usually leads to clonal dominance via multiple biological pathways and increases the risk of developing hematological malignancies. With the advancement of Next Generation Sequencing (NGS) technology, CH can be widely detected in healthy individuals, many patients complicated with bone marrow failure (BMF), or even in those with myeloproliferative neoplasm (MPN) and therapy-related MDS/AML (t-MDS/AML). Recently, several proof-of-concept studies showed that it is likely to discriminate the CH with high risk developing malignancy through predictive models many years before its onset. Additionally, it has been shown that the CH-related premalignant clones can be abated or eradicated through chemical or genetic measures in animal models, thereby providing an insightful idea for preventing leukemogenesis. However, in despite of these advancements, the clinical implication and early diagnosis of CH for predicting hematological malignancies remain to be more investigated. In this review, we will first review the brief history, risk factors and molecular mechanisms of CH. Then, we will discuss the involved biological process of CH in bone marrow failure diseases, MPN and t-MDS/AML, pointing to its clinical implication. Finally, we will discuss the advancement of early detection of CH at premalignant stage for predicting hematological malignancies, and express perspectives and challenges for early intervention of CH in the future. Highlights: The concept, brief research history, risk factors and molecular mechanisms of CH have been introduced and reviewed systemically for a comprehensive understanding on its basic science. The clinical implication of clonal hematopoiesis in the hematological disorders has been reviewed, highlighting the significance of CH in the pathogenesis and progression of hematological malignancies. The rationality, potentiality and challenges for early detection and intervention of CH with high risk developing hematological malignancies have been analyzed and reviewed comprehensively..